Zespół akt dekanatu szadkowskiego w zasobie Archiwum Diecezjalnego we Włocławku. Część I - Szkutnik, Piotr (Biuletyn Szadkowski, 2010)
This contribution presents the documents and records relating to the  Szadek decanate, forming a separate file in the archives stored in the Diocesan Records Office in Włocławek. It first outlines the life and work of the author of these archives, and then describes their form and content. Legal regulations constitute the main part of the records; documents describing the decanate are much less numerous.